Statistical analysis of situations in sport - Virba, Viliam; Danko, Jakub; Kováč, Stanislav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Bachelor thesis offers insight into the specific sport situations from the statistic perspective that is possible due to availability of large amount well structured data that measure many aspects of the games. Every situation is present in American football and data are exclu- sively sourced from National Football League since 2000. American football as a sport is introduced followed by dataset description. After the league itself and dataset is described three hypotheses are formulated. First is trying to show how aggressive tactics could conse- quently lead to losing in tight games. Second hypothesis looks at the frequent event that is taking a timeout before opposing team is trying to score an important points by kicking a field goal. Last third hypothesis is trying to measure effect of stadium altitude on distance that is possible to be kicked by punter. Hypotheses are evaluated by statistical hypotheses testing after data are processed in desirable condition
Vedoucí práce: Jakub Danko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: datové analýzy a modelování [obor bakal. práce]; bakalářské práce; bachelor's theses